Religious musical performance as an articulation of transformation : a study of how the Tsonga Presbyterians of the Presbyterian Church of Mozambique negotiate their indigenous Tsonga and Swiss reformed church heritages - Germiquet, Nicole Madeleine (Rhodes University, Faculty of Humanities, Department of Music and Musicology, 2015)
The Presbyterian Church of Mozambique (IPM) has its origins in the Swiss Mission and the European Reformed Church. An ethnomusicological study was conducted on the music of the IPM in order to uncover its musical influences. The musical influences were found to pertain to an indigenous Tsonga musical character, as well as to a Reformed Church musical tradition. By situating the discussion in this thesis within the perspective that music may reflect that which is not explicitly spoken about in words, the music of the IPM was shown to reflect the dual-heritage of the members of the IPM. Thus, this thesis attempts to answer the questions: how is the music of the IPM a reflection of the Tsonga Presbyterians' dual-heritage?; and how do the Tsonga Presbyterians negotiate their dual-heritage? It was found that the Tsonga Presbyterians negotiate their dual-heritage by blending a Reformed Church performance style with a Tsonga one. For example, the music in the form of hymns and church songs, performed by church choirs, is shown to be didactic in nature where the lyrics are the most important aspect of the music. The didactic nature of the music is a principle of the Reformation carried forth in the music of the IPM. Although music serves to transmit the Christian message and is used as a means of praising the Christian God in the IPM, it also exists on the level in which the indigenous Tsonga heritage may be incorporated into the Christian lives of the members of the IPM without having an impact on the Reformed Church belief system. This is where the members have the freedom to blend their musical heritages. Music, in this instance, is shown to be a powerful tool by which the importance of an indigenous, and an appropriated, heritage may be garnered and observed.Looking to the historical aspects of the IPM, the music and language literacy education, provided by Swiss missionaries on the mission stations, was shown to have had an influence on Tsonga hymn composition. Along with the mobile phone, the observed decrease in music literacy at Antioka was situated within a discussion that looked at the influence of these aspects on the transmission, conservation and continuation of music in the IPM. Throughout the thesis, social transformation is referred to and the manner in which the music of the IPM is conserved or continued is an indication of how musical transformation may reflect social transformation.
Keywords: Igreja Presbiteriana de MocÌ§ambique; Sacred music -- Mozambique; Church music -- Mozambique; Church music -- Presbyterian; Tsonga (African people) -- Mozambique -- Music; Ethnomusicology; Church music -- Cross-cultural studies